Faktor-Faktor yang Mempengaruhi Nilai Perusahaan Manufaktur di Indonesia - Nengsi, Rahma (LPPM Institut Nasional Laa Roiba Bogor, 2024)
This study aims to examine the effect of Return On Asset, Debt to Equity Ratio, Current Ratio, Total Asset Turnover, and Price Earning Ratio on firm value. The research was conducted on 196 manufacturing companies listed on the Indonesia Stock Exchange during the period 2020-2022. A sample of 77 companies was selected with purposive sampling method. This research uses quantitative method and panel data regression analysis using the Eviews Version 12 software to determine the relationship between variables. The results showed that partially Return On Asset, Debt to Equity Ratio, Current Ratio, and Price Earning Ratio have a positive and insignificant effect on firm value. While Total Asset Turnover has a negative and insignificant effect on firm value. Then, simultaneously Return On Asset, Debt to Equity Ratio, Current Ratio, Total Asset Turnover, and Price Earning Ratio have an significant effect on firm value.